Optimization Of Outgoing Product Selection In A Warehouse Information System Using The First Expired First Out Method - Tegar Mallisa; Umar Zaky (Universitas Ibn Khaldun Bogor, 2025)
A Bambu Runcing Petshop is a pet shop that provides animal needs such as food, vitamins, and medicines. This store faces obstacles in determining outgoing products, especially products that have an expiration date. The absence of a system that prioritizes issuance based on expiration date risks causing expired products to remain issued. For this reason, a Warehouse Information System was developed using the First Expired First Out (FEFO) method to optimize the determination of outgoing products. System development uses the Waterfall approach with data collected through observation, interviews, and literature studies. The test results show that the application of the FEFO method in the warehouse information system was successfully run with a 100% success rate in 5 test scenarios using the black box method, where the system automatically selects and releases products based on the nearest expiration date. Thus, the warehouse information system is able to support the determination of outgoing products to be more optimal and can reduce the risk of loss due to expired products.